Cord Blood pH and Lactate- A Step Ahead in Diagnosis of Fetal Acidaemia in Patients with Abnormal Cardiotocography - Mukhopadhyay, Indrani; Singh, Sanjay; Kachatti, Sushila (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVES: Electronic fetal monitoring (EFM) is used to identify early signs of fetal deterioration. However, caution is advised when interpreting cardiotocographic parameters. A promising alternative is umbilical cord blood sampling. The analysis of blood gases and lactate levels in the cord within the ini-tial minutes of life is a recommended approach. STUDY DESIGN: This prospective cohort study, conducted over eighteen months from June 2021 to December 2022, enrolled 70 patients with non-reactive and 70 with reactive cardiotocograph (CTG) pat-terns. APGAR scores were recorded at 1 and 5-minute intervals. 1 ml of umbilical artery blood was as-sessed in an arterial blood gas machine and fetal acidosis was defined as pH <7.0 and a lactate con-centration exceeding 4 mmol/L. RESULTS: In the non-reactive CTG group, 35.7% had early decelerations, 37.1% had variable decel-erations, and 17.1% had late decelerations (p<0.001). The mean cord blood lactate was 5.220±1.970 mmol/L in the non-reactive CTG group and 3.400±0.228 mmol/L in the reactive CTG group. Similarly, the mean cord blood pH was 7.030±0.007 in the non-reactive CTG group and 7.170±0.076 in the reac-tive CTG group (p<0.001). 14.3% of cases in the non-reactive CTG group had a 5-minute APGAR <7, with a higher APGAR score in the reactive group. CONCLUSION: The study suggests that abnormal or indeterminate CTG readings are linked to a higher risk of intrapartum fetal acidosis. Non-reactive CTG results were associated with higher mean cord blood lactate and pH levels and more number of Neonatal Intensive Care Unit (NICU) admissions. There is a definite correlation between abnormal CTG patterns and poorer neonatal outcomes.